Determinants of vulnerability of bean growing households to climate variability in Colombia - Pérez Marulanda, Lisset; Ríos, David; Giraldo Mendez, Diana Carolina; Twyman, Jennifer; Blundo Canto, Genowefa M.; Prager, Steven D.; Ramírez Villegas, Julián Armando (International Center for Tropical Agriculture, 2018)
Data collected using household surveys applied to bush bean farmers in municipalities of Barichara, Villanueva, Curiti and San Gil in the department of Santander, Colombia. Socioeconomic, Farm related and climate perception data were collected with the aim to assess the climate vulnerability and its determinants of bush bean farmers in the region. Some climate variable were constructed using data from CHIRPS.